2017
DOI: 10.1371/journal.pone.0188199
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Th17 cytokines and interleukin-22 correlates with disease activity in pristane-induced arthritis in rats

Abstract: The objective of this study was to identify the key changed subtype of T helper cells (Th cells) and their cytokines in pristane-induced arthritis (PIA) in rats. The severity of arthritis was evaluated by body weight, clinical score, the perimeter of ankle and mid-paw and histological assessment of ankle joints. Cytokines of Th1, Th2 and Th17 were determined in the spleen and inguinal lymph nodes at 28 days after pristane injection by real-time qPCR. The mRNA levels of IL-22 receptors, IL-22R1 and IL-22BP, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
(67 reference statements)
1
5
0
1
Order By: Relevance
“…12 PIA is one of the extensively used models for research purpose due to appreciative resemblance to the chemical characteristics of RA. 13 It is similar to the condition seen in humans due to the presence of symmetrical joint involvement, presence of rheumatoid factor, bone and cartilage destruction as well as dependence of specific immunity seen in such models. 14 In the present study the results indicated that the development of arthritis correlated with the increase in arthrogram score, TLC and histological score in Group B as compared to the Group A (normal control) till day 14.…”
Section: Discussionsupporting
confidence: 54%
“…12 PIA is one of the extensively used models for research purpose due to appreciative resemblance to the chemical characteristics of RA. 13 It is similar to the condition seen in humans due to the presence of symmetrical joint involvement, presence of rheumatoid factor, bone and cartilage destruction as well as dependence of specific immunity seen in such models. 14 In the present study the results indicated that the development of arthritis correlated with the increase in arthrogram score, TLC and histological score in Group B as compared to the Group A (normal control) till day 14.…”
Section: Discussionsupporting
confidence: 54%
“…Among different cytokines that this Th17 subtype produces is granulocyte-macrophage colony-stimulating factor (GM-CSF), or IL-22. Some studies have shown that the signaling pathway of IL-22 (GM-CSF) may be activated in RA pathogenesis [34,35].…”
Section: T Cell-mediated Immune Response In Ramentioning
confidence: 99%
“…The human IL-22 gene is found on the 12q15 chromosome in addition to the IFN-γ and IL-26 genes [ 98 ], and is produced by Th17 [ 56 ] and Th22 cells. The production of IL-22 is promoted by IL-17, IL-23, IL-1β, aryl-hydrocarbon receptors (AhR), and Notch signaling [ 99 ]. The IL-22R is a complex of IL-22R1 and IL-10R2 containing an intracellular, transmembrane, and extracellular signaling region.…”
Section: Interleukin-22mentioning
confidence: 99%
“…The concentration of IL-21 was higher in PIA rats but was not significant compared to IL-22. In this study, IL-21 only supported Th17 differentiation and enhanced their response [ 99 ]. The same group showed that in PIA rats, the level of IL-22 expression was different in different phases of PIA.…”
Section: Interleukin-22mentioning
confidence: 99%